Heavy Metal Assessment of Kavre Valley Basin River System - Shakya, Siddhartha; Gurung, Prekshya; Bohaju, Anjal; Ojha, Dipson; Kafle, Bhim Prasad (Hydro Nepal: Journal of Water, Energy and Environment, 2019)
Recent population growth, industrialization and unplanned urbanization have led to an increase in untreated waste disposal directly to the river system, including heavy metals. The present investigation was conducted for assessment of heavy metals in the Kavre valley river basin system. Through this basin, two major rivers Punyamata and Roshi along with their tributaries, flow passing through cities (Banepa, Shree Khandapur and Panauti) and the heavy metals selected were Iron (Fe), Chromium (Cr), Manganese (Mn), Lead (Pb), Zinc (Zn) and Cadmium (Cd). Seven sites were selected on the basis of city size and meeting point of tributaries. Fe, Cr and Mn were examined using UV-spectrophotometry whereas Pb, Zn and Cd were determined using AAS. The highest concentration of Cr, Mn, Fe, Cd, Zn, Pb were determined to be 1.9 μg/L, 22.6 μg/L, 514 μg/L, 340 μg/L, 20 μg/L, 80 μg/L, respectively, with Fe, Cd and Pb exceeding the WHO limits.